Construction of stable LamB-Shiga toxin B subunit hybrids: analysis of expression in Salmonella typhimurium aroA strains and stimulation of B subunit-specific mucosal and serum antibody responses. - Su, G F (1992)
The complete Shiga toxin B subunit and two N-terminal segments of the B subunit have been inserted into a cell surface exposed loop of the LamB protein, and expression of the hybrid proteins from three different promoter systems, i.e., (i) an in vitro-inducible tac promoter that provides high-level expression, (ii) the iron-regulated aerobactin promoter presumably induced in vivo under the iron-limiting conditions of the intestinal mucosal environment, and (iii) a synthetic, modified beta-lactamase promoter providing moderate level constitutive expression, has been analyzed in Escherichia coli, Salmonella typhimurium, and attenuated antigen carrier strains of S. typhimurium (aroA mutants). The hybrid vaccine strains were used to immunize mice by the oral and intraperitoneal routes. S. typhimurium aroA mutants apparently have a membrane export defect which prevents the transport of LamB and its derivatives across the cytoplasmic membrane. High-level expression of hybrid proteins through use of the tac promoter proved deleterious to the vaccine strains and prevented the production of viable cells at reasonable cell densities. The lower levels of gene expression observed with the beta-lactamase and aerobactin promoters did not have this effect. Immunization of mice with S. typhimurium aroA strains carrying the hybrid genes expressed from these two promoters resulted in significant B subunit-specific mucosal and serum antibody responses. This suggests that such expression systems may be useful when incorporated into candidate antidysentery live oral vaccines for inducing protection against the effect of Shiga toxin in infections caused by Shigella dysenteriae 1 and other Shiga toxin-or Shiga-like toxin-producing pathogens.